Comprehensive School Physical Activity Programming and Health Behavior Knowledge - Mattson, Rose E.; Burns, Ryan D.; Brusseau, Timothy A.; Metos, Julie M.; Jordan, Kristine C. (Frontiers in Public Health, 2020)
No study to date has examined the effect of a multicomponent school-based physical activity program on health behavior knowledge in a large sample of low-income children from the US. The purpose of this study was to explore the change in physical activity and nutrition knowledge during a Comprehensive School Physical Activity Program (CSPAP) in children. Participants were a convenience sample of 789 children recruited from the 4th to 6th grades from five low-income Title I schools located within the Mountain West Region of the US. Students completed two questionnaires consisting of a physical activity and a nutrition knowledge assessment. Questionnaires were administered at baseline before the commencement of CSPAP and at a 36-week follow-up. Data were analyzed using a 3  2  2 doubly MANOVA test. Physical activity knowledge scores significantly improved from pretest to posttest during the intervention (p = 0.045, Cohen’s d = 0.18). Grade level modified the time effects, with older children in grades 5 and 6 displaying greater improvements in physical activity knowledge than younger children in grade 4 (p = 0.044, Cohen’s d = 0.33). There were no significant improvements in nutrition knowledge scores during the CSPAP (p = 0.150). These findings demonstrate that improvements in physical activity knowledge can occur during a multicomponent school-based intervention. Improvements in physical activity knowledge may translate to improvements in habitual physical activity behaviors and positively influence children’s health outcomes, especially in older children.